2000
DOI: 10.2307/2676306
|View full text |Cite
|
Sign up to set email alerts
|

Of Fear and Loathing: The Role of 'Disturbing Behavior,' Labels, and Causal Attributions in Shaping Public Attitudes toward People with Mental Illness

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
414
6
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 548 publications
(484 citation statements)
references
References 41 publications
36
414
6
15
Order By: Relevance
“…When comparing the attitudes of our participants with those of other studies conducted with the general population, attitudes of fear, dangerousness, responsibility for the condition, and avoidance seem to have been less frequent in our study. [33][34][35][36][37][38] Notwithstanding, other studies conducted with relatives of people with severe mental illness have also confirmed a low level of perceived dangerousness, similarly to our study. 39 The attitudes of our family members seem to be oriented towards providing support and assistance to the mentally ill, although they do consider compliance to pharmacological treatment and regular medical visits as essential for the patient's well-being, even if against the patient's own will.…”
Section: Discussionsupporting
confidence: 91%
“…When comparing the attitudes of our participants with those of other studies conducted with the general population, attitudes of fear, dangerousness, responsibility for the condition, and avoidance seem to have been less frequent in our study. [33][34][35][36][37][38] Notwithstanding, other studies conducted with relatives of people with severe mental illness have also confirmed a low level of perceived dangerousness, similarly to our study. 39 The attitudes of our family members seem to be oriented towards providing support and assistance to the mentally ill, although they do consider compliance to pharmacological treatment and regular medical visits as essential for the patient's well-being, even if against the patient's own will.…”
Section: Discussionsupporting
confidence: 91%
“…So I have a great deal of sympathy. (25, M, 55-64) Studies have reported addictions to be more negatively perceived than other mental illnesses Link et al, 1989;Martin, Pescosolido, & Tuch, 2000), with drug addiction generally more highly stigmatized than alcohol and gambling addictions, which have been found to attract similar levels of stigma (Arbour-Nicitopoulos, Faulkner, Paglia-Boak, & Irving, 2010;Horch & Hodgins, 2008). Addictions tend to be highly stigmatized because affected individuals are perceived as blameworthy for their disorder (Angermeyer & Dietrich, 2006), despite having impaired control over their addictive behaviour.…”
Section: Perceived Origin Of Problem Gambling and Other Dimensionsmentioning
confidence: 99%
“…It may also point to strategies for recovery. Nevertheless, a potential problem associated with belonging to this group is that there are stereotyped beliefs attached to severe mental illness (Martin et al, 2000;Swindle et al, 2000). Categorically referred to as stigma, these beliefs are spread across all levels of society and include expectations of violent and disorderly behavior as well as the conviction that persons with schizophrenia cannot work or make informed decisions about their welfare (Link et al, 1999;Phelan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%